Mnohoproblémové romské rodiny a jejich ochrana dětí před riziky - Caltová Hepnarová, Gabriela (Romano džaniben, 2017)
The article presents the partial results of the research investigation which focused on the educational effect of Romani parents in the so-called multiproblem families. The research had revealed a few important areas, for example, a way of experiencing the parental concerns, risk identification and parental child protection strategy itself. The main aim of this text is to introduce the range of concerns, risks, and protective procedures that parents elect. Among the captured parenting practices direct control in the domestic environment, the pursuit of the isolation of the children but also checking information was found to dominate. In parallel with these procedures, the parents were trying constantly to build a close relationship with their children,which they considered the surest guarantee that the child could handle all the risks.